Intervensi Metode Sedap (Sharing, Education, And Practice) Dalam Meningkatan Kualitas Hidup Pada Pasien Tuberkulosis Paru Di UPT Puskesmas Tanjung Rejo Desa Percutsei Tuan Deli Serdang - Harahap, Solihuddin; Lestari; Yusdiana, Dina (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
ABSTRACT Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis bacteria. Implementation methodology by providing health education materials using lecture techniques and providing leaflets to the community: (1) Prevention attitude of pulmonary TB respondents before education was given, the majority of respondents had an unfavorable attitude as many as 21 respondents (65.6%). (2) Knowledge of pulmonary TB respondents before education was given, the majority of respondents had poor knowledge as many as 22 respondents (68.8%). (3) Based on the sharing of TB patients and their families, the majority of respondents have never dropped out of medicine, do not understand saliva, how TB is transmitted to the family and how to process the home environment. (4) Prevention attitude of respondents after providing education, the majority of respondents had a good attitude after being given education as many as 26 respondents (81.3%). (5) Respondents' knowledge after providing education, the majority of respondents had good knowledge after being given education as many as 26 respondents (81.3%) (6) Hand Washing Education Practices Cough Ethics Education Practices the majority of respondents were not perfect in carrying out cough ethics education practice activities as many as 19 respondents (59.4%) and the majority of respondents were not perfect in carrying out hand washing education practice activities as many as 17 respondents (53.1%). (7) Practice of Spitting The majority of respondents' ability to carry out this practice was evenly divided, with 16 respondents (53.1%). Keywords: Tuberculosis, SEDAP Method, Quality of life, knowledge